Using Azolla microphylla in investigating different agro-wastewaters treatment and its biomass growth for carbon sequestration - Nyein Nyein; Chuleemas Boonthai Iwai (Results in Engineering)
Nowadays, the challenges of global warming and scarcity of natural water resources have heightened the importance of developing sustainable solutions that are affordable, energy-efficient, and eco-friendly. The increased population and food demand have led to a significant expansion in the livestock and aquaculture sector, generating considerable quantities of solid waste and wastewater that affect the ecosystem and human health. The present study aimed to assess the dual potential of Azolla microphylla in agro-wastewater treatment and carbon sequestration from the atmosphere. This research aimed to monitor the water quality parameters and evaluate the growth performance and carbon capturing of A. microphylla. The experiment was conducted by using a completely randomized design with agro-wastewaters from different sources, including 5 % swine wastewater (5 %SW), poultry wastewater (PW), and aquaculture wastewater (AW). The aquatic plant A. microphylla was employed for this experiment. After two weeks of experiment, the highest BOD removal, 83.3 %, and COD removal, 82.1 %, were observed in 5 % SW and PW, respectively. Notably, the removal efficiency of nutrients and pollutants in the experiments using A. microphylla was significantly higher than the control. According to the significant biomass production, the maximum carbon sequestration rate, 1.38 g CO2 per g Azolla (dry weight), was observed in PW. The study concludes that biomass transformation of A. microphylla in agro-wastewaters could be the eco-solution for both phytoremediation in wastewater treatment and carbon sequestration in eliminating atmospheric carbon dioxide.